"Nie waar nie?" Opmerkinge oor geloofservaring, dogma en die (eskatologiese) aard van teologiese besinning - Veldsman, D. P. (Verbum et ecclesia, 2008)
"Not true?" Remarks on the experience of faith, dogma and the (eschatological) nature of theological reflection "Not true?" is a characteristic saying of Conrad Wethmar. In this article of appreciation for his academic contribution, this saying as a "polite questioning and affirmation" (as I understand it), is explored within the context of viewpoints on the experience of faith and in reference to his understanding of dogma in order to highlight the way in which this saying actually gives expression to his understanding of the nature of theological reflection.